Revising the conventional tax‐effort principle. (26th December 2019) - Dalamagas, Basil; Leventides, John; Palaios, Panagiotis; Tantos, Stefanos
Abstract: The standard methodology on tax‐effort (i.e., the ratio of actual tax revenue to its optimal level) is to run a regression of actual tax revenue on countries' specific (macroeconomic, demographic, geographical, political, social, and institutional) variables. The resulting predicted (fitted) values are then taken to represent the optimal (desired or maximum) level of tax revenue. The crucial issue of tracing out how the optimal tax revenue should be allocated to the fiscal objectives (equity, efficiency) does not seem to be of any interest to the researchers on tax‐effort. The present paper argues that the standard methodology is not without faults and needs revising. We demonstrate that an optimal tax system can be safely derived from maximizing a utility function with respect to (in)direct tax rates. The manipulation of the first‐order conditions, using a novel mathematical module, leads to an infinite number of optimal direct–indirect tax rates. The selection of the optimal mix of these tax rates is dependent on the country‐specific households' preferences over equity/efficiency, as they are formulated by voters' volition in election periods. A simulation procedure helps understanding how the optimal tax revenue is chosen and how it can be optimally allocated to fiscal objectives, in the context of a panel data set including a large number of developed and developing countries. Throughout our text, the optimal tax revenue is defined as the sum of the products of the optimal (in)direct tax rates and their corresponding tax bases. In the simple Arrow–Debreu economy, the above sum is shown to be equal to the difference between income and consumption.